THU0137 Impact of periodontal and rheumatic disease markers on first-degree relatives of patients with rheumatoid arthritis according to age group. (15th June 2017) - Romero-Sanchez, C; Giraldo, S; De-Avila, J; Cano-Bermuedez, MA; Chila-M., L; Bello-Gualtero, J; Chalem, P; Bautista, W; Londono, J; Pacheco-Tena, C; Lafaurie, G; Valle-Oñate, R
Abstract : Background: Rheumatoid arthritis (RA) and periodontal disease (PD) have similar underlying pathologic processes and share a general deregulation of the inflammatory response. Objectives: To evaluate PD markers in first-degree relatives (FDR) of consanguinity individuals of patients with rheumatoid arthritis to compared with controls and to establish an association to rheumatic activity according to age groups Methods: 201 FDR individuals and 201 matched controls were included. Clinical evaluation of rheumatologic and periodontal condition was performed. P. gingivalis, P. gingivalis IgG1 and IgG2, ESR, CRP, RF, ACPAs, painful and swollen joints were assessed. A frequencies analysis, comparisons and a logistic regression model were made. The study was approved by local ethics committee. Results: 37.3% of patients with overweight and 10.1% obsesses. Subjects with more than one swelling joint were 21 subjects <30 years, 5 between 31–40, 5 between 41 to 50 subjects and 9 subjects over 50, for more one painful joint were 73. The RF was present in 8.0%, APCA in 13%, RA33 in 1%. 67.3% had a diagnosis of PD, 81.6% had a moderate-severe p=0.003. P. gingivalis was in 47, 9%, and P. gingivalis IgG1 were in 54.7%. It was evidenced that 25.3% patients presented BMI>30, where 81.8% had periodontitis p=0.006. Regression analysis on the whole group shows a risk to present BMI>25 (OR 1.67 IC-95% 1.02 – 2.74 p=0.042), ACPAs (OR 3.7 IC-95% 1.34–10.22 p=0.012), at least one pain join (OR2.51 IC-95% 1.42–4.44 p=0.001) and gingival index (OR4.57 IC-95% 1.76–11.80 p=0.002) in FDR individuals. Based on age the risk to develop PD was increasing: individuals among 30 to 40 years shows OR 2.76 (IC-95% 1.24–6.18, p=0.013); among 41 to 50 years, OR 4.72 (IC-95% 1.81–12.32, p=0.001); and for >50 years individuals an OR 6.22 (IC-95% 2.55–15.1, p=0.0001). The discriminating analysis by age rank shows that FDR individuals <30 years (n=67) exhibited high risk to have at least one pain join (OR 3.84 IC-95% 1.28–11.47 p=0.016). In subjects among 30 to 40 years (n=46), the risk was associated with periodontal pocket (OR1.44 IC-95% 1.05–4.98 p=0.021), one or more pain join (OR 3.56 IC-95% 1.22–10.40 p=0.020) which it was maintained until 50 years individuals (n=35) (OR4.32 IC-95% 1.11–16.78 p=0.0034), individuals >50 years (n=53) show high risk to present BMI>25 (OR 4.00 IC-95% 1.46–10.45 p=0.007). Conclusions: Obesity, ACPA and periodontitis can be considered as relevant conditions associated with the development of RA in FDRs. However, the analysis based on age group shows that periodontal markers do not appear early in FDR individuals; however, clinical rheumatologic variables are manifested and maintained over time. References: Bello-Gualtero JM et al. J Periodontol 2016;87:346–356. Disclosure of Interest: None declared